Survey on Simulation for Mobile Ad-Hoc Communication for Disaster Scenarios - Marin-Caihuan, J; Bonacic-Castro, C; Rosas-Olivos, E; Hidalgo-Castillo, N (Springer New York LLC, 2016)
Mobile ad-hoc communication is a demonstrated solution to mitigate the impact of infrastructure failures during large-scale disasters. A very complex issue in this domain is the design validation of software applications that support decision-making and communication during natural disasters. Such disasters are irreproducible, highly unpredictable, and impossible to scale down, and thus extensive assessments cannot be led in situ. In this context, simulation constitutes the best approach towards the testing of software solutions for natural disaster responses. The present survey reviews mobility models, ad-hoc network architectures, routing protocols and network simulators. Our aim is to provide guidelines for software developers with regards to the performance evaluation of their applications by means of simulation. © 2016, Springer Science+Business Media New York.